Networking for strengthening design literacy - Brodshaug, Brodshaug; Reitan, Janne Beate (FormAkademisk, 2021)
This article focuses on design education for the general public and the ways in which students and teachers can become more design literate through the development of networks, such as professional groups for teachers. The aim of professional groups is to create a structure that focuses on design competency among Design, Art and Crafts teachers as well as design education in Norway’s primary and secondary schools. Etienne Wenger's theories of community of practice and Unn Stålsett's theory about the development of networking through professional groups are highlighted in this study through the comparison of two municipalities in conjunction with informant interviews. The emphasis of this study is on how each municipality gives time and space for the development of design competence through professional groups. A well-organized professional group will hopefully contribute to a deeper level of expertise in schools and an increased ability for the general public to recognize design education.